Factors Associated with the Incidence of Non-Communicable Diseases - Rini Puspasari; Khairun Nisa Berawi; Suharmanto Suharmanto; Aila Karyus; Sutarto Sutarto (Indonesian Journal of Global Health Research, 2026)
Non-communicable diseases (NCDs) are chronic diseases that are not transmitted between individuals. The course of these diseases generally progresses slowly, influenced by a combination of genetic, physiological, environmental, and behavioral factors. This study aims to analyze the relationship between lifestyle, physical activity, and exercise and the incidence of NCDs. This study used a cross-sectional approach. The study was conducted from August to September 2025 at the Ciloto Health Training Center of the Ministry of Health of the Republic of Indonesia. The population in this study was all 159 employees, and a sample of 141 respondents was selected using purposive sampling. Data were collected using a validated questionnaire with an r value in the range of 0.476-0.87 (valid) and a Cronbach's alpha value of 0.97 (reliable). Data analysis used the chi-square test. The results showed a relationship between lifestyle, physical activity, and exercise and the incidence of NCDs among BBPK Ciloto employees of the Ministry of Health of the Republic of Indonesia.